Analysis of Dominant Factors That Influence Public Dissatisfaction Indonesia In Service Public: Studies Meta- Analysis - Tia; Helmy; Aldy (LPPM STIES BABUSSALAM, 2026)
Public service dissatisfaction in Indonesia persists despite regulatory advances like Law No. 25/2009 and SPBE Presidential Regulation No. 95/2018, which aligns with New Public Service (NPS) principles emphasizing citizen-centered governance. This meta-analysis study identifies dominant factors influencing public dissatisfaction through a systematic literature review (SLR) and meta-analytic synthesis of empirical studies from 2019–2025. Following PRISMA guidelines, we searched databases (eg, Google Scholar) using keywords like